Initial Investment in Diversity Is the Efficient Thing to Do for Resilient Forest Landscape Restoration - Nef, Danny P.; Gotor, Elisabetta; Wiederkehr Guerra, Gabriela; Zumwald, Marius; Kettle, Chris J. (Frontiers in Forests and Global Change, 2021)
The genetic diversity, quality and suitability of seeds and planting stock is crucial for the short and long-term resilience of forest landscape restoration (FLR). However, these genetic aspects are widely neglected during both planning and implementation of restoration. Decisions on seed sourcing during implementation of FLR initiatives often prioritise short-term cost savings over long-term benefits. Such considerations result in strategies that favour rapid and cheap mass production of homogeneous plants and, thus, quantity over quality, with no regard for genetic diversity. This paper explores in detail the economic cost of improved integration of genetic diversity into restoration projects and tests the assumption that the benefits accruing from better integration of diversity exceed the costs. Using a bottom-up cost model, based on peer reviewed scientific literature, we analyse different FLR cost drivers, integrating genetic quality, in relation to the total costs of a range of tree-based restoration interventions, with a focus on seed sourcing and tree species selection. The results indicate that the integration of genetic diversity into the management and planning of landscape restoration projects increased the costs incurred at the beginning of FLR interventions, specifically during seed sourcing and species selection. These additional costs were largely due to the increased effort for the collection of genetically diverse and suitably adapted seed lots. However, despite this initial increase in costs the overall costs of restoration decreased substantially, due to cost savings relating to replacement costs of replanting. Even without these savings, the inclusion of genetic diversity is advisable since the costs involved in the integration of diversity are negligible compared to other restoration costs. We conclude that the expected long-term benefits associated with high genetic diversity far outweigh the costs. It also highlights that investing in genetic diversity as part of FLR is the smart thing to do to ensure cost effective and resilient landscape restoration. Restoration policies need to incentivise consideration of genetic diversity.